Discrete Valued Optimal Control Problems - An Overview - Rehbock, Volker (Universal Academy Press, Inc, 2007)
Discrete valued optimal control problems arise in a wide variety of practical applications.In this paper, we give an overview of this and various related classes of optimal controlproblems and point out a variety of practical examples. A number of solution methodshave been proposed in the literature and these will be reviewed with a particular emphasis on computational approaches.